Robot-assisted gait training after a stroke - Maric, Ivana; Trajkov, Marija; Kljajic, Dragana; Ilic, Milan (Education and Research in Health Sciences, 2024)
A gait disorder, which arose as a result of a stroke, leads to a significant disability. The main goal of neurorehabilitation is to restore the function of independent movement through conventional physiotherapy, but also the application of Robot-assisted Gait Training. The aim of this paper is to analyze the current use of robotic gait trainers in the rehabilitation of gait in people after a stroke. In clinical practice, there are different types of devices that are adapted for people, both in the subacute and chronic stages after suffering a stroke. Changes in gait function resulting from the use of robotic gait trainers, such as increases in gait speed, stride length, and spatial symmetry, are evident in clinical practice. However, there is a lack of follow-up evaluations and long-term effects, as well as risk assessment of the use of these devices in gait rehabilitation in people after a stroke.